Ancash, diagnosis for a strategy - Cetraro Cardó, César (2008)
As in previous works on the regional reality already published in the IECOS Magazine, the author offers an overview of the department of Ancash, where after the geographical and political-administrative description, the available infrastructure works and the population are indicated. Deficiencies in employment and social services (health and education) are shown and concludes with a review of the economy and productive opportunities in each sector. He once again highlights the interest in attending first to the needs of populations with fewer resources.